Manajemen Waktu Pembelajaran Daring Di Masa Pandemi Covid-19 Pada TK Dharma Wanita 1 Baleturi - Ana Ulin Nadhirin; Agus Miftakus Surur (As-Sibyan: Jurnal Pendidikan Anak Usia Dini, 2020)
This study aims to determine the time management of online learning in Kindergarten (TK) Dharma Wanita 1 Balleturi. The importance of learning time management is because it has many impacts such as having clear priorities, reducing delays, being on time in doing work so that it can increase satisfaction in doing tasks, having the ability to keep concentrating on tasks so as to increase productivity, and being able to practice disciplinary habits for this. That relates to time so that the task will be carried out more efficiently. This research is a qualitative research, using data collection techniques such as observation, interviews, and documentation. The result of this research is that the fulfillment of aspects of time management can assist in the management of the online learning process. These aspects are setting goals, setting priorities, setting schedules, being assertive, being assertive, avoiding procrastination, minimizing wasted time, and controlling time.